Avaliação da qualidade da água de uma microbacia hidrográfica rural dos tabuleiros costeiros do Brasil - Silva, Karina Ribeiro da (2020)
The evaluation of water quality is an important tool to support the management of water resources and essential to identify anthropogenic and / or natural changes that occur in a hydrographic basin. The main objective of this work was to evaluate the water quality of the Timbó stream watershed, sub-basin of the Poxim-SE river. In this sense, four water collections were carried out in the period between June 2018 and August 2019 at three sampling points. The collections and analyzes of the water were carried out according to the procedures established in the Standard Methods for the Examination of Water and Wastewater for the parameters: temperature, turbidity, electrical conductivity, pH, chlorophyll a, OD, BOD, STD, total solids, coliforms thermotolerants, COT, Ptotal, N-NH3, NO2 - , NO3 - , SO4 2-, Cl- , Ca2+, Mg2+, K+ and Na+ . The results found were analyzed using descriptive statistics techniques, parametric mean tests, used to verify the existence of differences between the water quality values observed at the three different collection points and between the different dates, and by multivariate analyzes. The results obtained showed that the average concentrations of DO (5.68 mg L-1), BOD (3.45 mg L-1) and thermotolerant coliforms (407.61 NMP 100mL-1) did not fit the standards established for class 1 freshwater, however, are within the limits for the other classes, established in CONAMA Resolution 357/2005. Regarding the Water Quality Index (63), the water body was classified as of good quality. The statistical analysis showed that the water parameters analyzed did not show any significant difference between the collection points, however, it shows the influence of rainfall in some parameters, with emphasis on pH, STD, Ptotal, N-NH3, Cl- , Na+ , SO4 2- and DBO. Thus, it was evident that the physical, chemical and biological characteristics of waters in the watershed are influenced by natural factors, causing reflections on the quality of the investigated water body.